Search for CP violation in the phase space of D0 → π−π+π0 decays with the energy test - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; Langenbruch, Christoph; et al. (Journal of high energy physics, 2023)
A search for CP violation in D0 → π−π+π0 decays is reported, using pp collision data collected by the LHCb experiment from 2015 to 2018 corresponding to an integrated luminosity of 6 fb−1. An unbinned model-independent approach provides sensitivity to local CP violation within the two-dimensional phase space of the decay. The method is validated using the Cabibbo-favoured channel D0 → K−π+π0 and background regions of the signal mode. The results are consistent with CP symmetry in this decay.